¿Quieren los españoles una democracia (más) participativa ? - Mathias Rull Jan (Les Cahiers de Framespa)
The article aims to help determine, in Spain at the beginning of the 21st century, the extent to which citizens want to be directly involved in political decision-making (and no longer only in the election of authorities). It is based on several factual elements that have given the Spanish, with regard to their European neighbours, the reputation of being particularly inclined towards citizen participation. In order to verify this appearance, the article discusses three factors that make it possible to identify more precisely the participatory aspirations of Spaniards: the general value they attach to citizen participation; the origin of democratic innovations implemented in Spain during the first decade of the century; and finally the importance of party proposals in terms of citizen participation in determining the vote. The analysis of these three criteria leads the author to minimize the importance of the social demand for citizen participation in Spain today.